2015
DOI: 10.5114/reum.2015.53994
|View full text |Cite
|
Sign up to set email alerts
|

The initial ultrasonographic examination of hands and feet joints in patients with early rheumatoid arthritis

Abstract: Objectives: The aim was to assess of the morphology, intensity, and activity of changes in the first ultrasonographic (US) examination of hands and feet in patients with early arthritis (lasting up to 12 months) who were ultimately diagnosed with rheumatoid arthritis (RA). An attempt was made to demonstrate a correlation between the intensity of lesions in US and selected laboratory parameters. Material and methods: Ultrasonographic examination was performed using a LOGIC GE 500 device on a group of 60 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The reason may be a rather low mean CRP value in this group of patients. In our previous study we demonstrated that higher CRP values were correlated with higher values of the PD index [15].…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be a rather low mean CRP value in this group of patients. In our previous study we demonstrated that higher CRP values were correlated with higher values of the PD index [15].…”
Section: Discussionmentioning
confidence: 99%